The American sea : a natural history of the Gulf of Mexico - Darnell, Rezneat M. (Harte Research Institute for Gulf of Mexico Studies series., 2015)
For more than a decade, Rezneat Darnell worked on this major synthesis of what is known about the Gulf of Mexico. His goal: to bring a deeper understanding of "the American Sea" to students, scientists, managers, and educated citizens of the public at large. The American Sea builds on Darnell's own research, the research of his graduate students, government agency research reports, data synthesis reports, and literature summaries to present a holistic view of the Gulf of Mexico. Although he is recognized as a pioneer in the study of continental shelf ecology, Darnell largely resisted specialization, remaining throughout his career "the writer and bringer together of things." Here, he has written a book that embraces history, geology, geography, meteorology, chemistry, biology, ecology, and human relations in one comprehensive reference. Although it is thorough and meticulous in coverage, what comes through in these pages is the enormity, complexity, and mystery of the world that lies just beyond the Texas vacation beach, the Louisiana wetland, or the Mexico fishing village. In addition to photographs of deep water and other organisms that are included in the book, a number of illustrations have been added to provide excellent visual material, including historical and ocean floor maps and many works of original art depicting marine species, sea turtles, fish, and crustaceans.